Complex Systems—A New Paradigm for the Integrative Study of Management, Physical, and Technological Systems - Amaral, Luis A. Nunes; Uzzi, Brian (Management Science, 2007)
In this introductory note, we describe the motivation for this special issue on complex systems. We begin by noting the potential management opportunities offered by recent advances in complexity science. After defining the nature of complex systems and the many ways they are expressed in organizations and markets, we briefly describe the main tools and concepts of complexity theory. We close with a brief review of the articles in this issue and their relevance to the interests and concerns of managers.